Pharmacy education symposium: a need of time - Nik Mohamed, Mohamad Haniki; Shamsudin, Siti Hadijah; Jamshed, Shazia Qasim (World Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Pharmacists are important among healthcare professionals because of their role in the identification and treatment of minor illnesses and counsel for major diseases irrespective of age, race, gender, and socioeconomic status and health convictions. Within the last five decades there is colossal entry of medications into the pharmaceutical market, thus accelerating the requirement of the pharmacists. The existing position of the pharmacist in a wider standpoint is that of a “seven star pharmacist” and thus pharmacy institutions are struggling to exercise principal influence in training students into full-fledged seven star pharmacists. Pharmacists being the health information custodian and the third largest group of health care providers seep into the changing dynamics of healthcare environment where now patient is both demanding and receptive for information even on minor illnesses [1]. To be precise the profession of pharmacy embraces the concept of ‘Patient centered Care’ thus changing the image of a pharmacist from a ‘dispenser’ to a ‘decision maker’ and ‘caregiver’. However, more work is needed to be done to establish the true value of this underrated healthcare professional group in the eyes of other stakeholders; be it a doctor, nurse, or a patient. In the backdrop of this, there is an urgent need to continuously revisit the principles of pharmacy education for better competency skills. Therefore, the Council of Deans for the Malaysian Public Pharmacy Schools and Kulliyyah of Pharmacy, International Islamic University Malaysia (IIUM)planned to organize a symposium, which was held in September 2013 at Conference Room, Cultural Activity Center (CAC), IIUM, Gombak Campus, Kuala Lumpur, Malaysia. This was attended by 34 delegates from different public universities in Malaysia, including Deans, Deans’ representatives, and pharmacy academics. The key speakers were Deans of the Malaysian Public universities. The five a priori themes on which the speakers embarked upon were Academic, Research, Community Services and Industrial Linkages, Student Activities and Internationalization.